Health-Related Quality of Life and Influencing Factors in Coronary Heart Disease Based on the Scale QLICD-CHD (V2.0): A Cross-Sectional Study - Rao S; Xu C; Wan C; Huang Z; Huang X; Chen S (International Journal of General Medicine, 2023)
Shuying Rao,1 Chuanzhi Xu,2 Chonghua Wan,1 Zhiwen Huang,3 Xingping Huang,4 Shu Chen1 1Research Center for Quality of Life and Applied Psychology, School of Humanities and Management, Guangdong Medical University, Dongguan, People’s Republic of China; 2Department of Statistics, School of Public Health, Kunming Medical University, Kunming, People’s Republic of China; 3Cardiovascular Department, the Affiliated Hospital of Guangdong Medical University, Zhanjiang, People’s Republic of China; 4Department of Research and Teaching, Dongguan Eighth’ Hospital, Dongguan, People’s Republic of ChinaCorrespondence: Chonghua Wan, Tel/Fax +86-0769-22896255, Email wanchh@hotmail.comPurpose: Coronary heart disease (CHD) is difficult to cure, so more attention should be paid to improving patients’ health-related quality of life (HRQoL). This paper focuses on identifying factors that affect HRQoL.Patients and Methods: Overall, 189 in-patients with coronary heart disease were investigated at the Affiliated Hospital of Guangdong Medical University between 2015 and 2016. The scale Quality of Life Instruments for Chronic Diseases-Coronary heart disease (QLICD-CHD V2.0) was used to evaluate HRQoL and collect demographic information. Medical records were applied to collect patients’ clinical indicators. A simple correlation analysis, Student’s t-test, and a one-way analysis of variance were first performed to filter factors that might associate with HRQoL, and multiple linear regression was applied to finally identify related factors.Results: Findings from multiple linear regression showed that the total score was related to family economy, treatment, indirect bilirubin, and albumin with regression coefficient B=5.209, − 6.615, 0.378, and 0.548, respectively. The physical functions were related to treatment, albumin, globular proteins, chloride, and red blood cell count with B=− 9.031, 1.000, 0.612, 1.320, and 5.161, respectively. The psychological function was in association with family economy, clinical course, serum phosphorus, and percentage of lymphocyte population with B=7.487, 6.411, − 16.458, and 0.090, respectively. The social function was associated with family economy, blood urea nitrogen, serum creatinine, and platelet distribution width with B=7.391, 1.331, − 0.060, and − 0.929, respectively. The special module was in association with treatment, indirect bilirubin, and serum calcium with B=− 7.791, 0.414, and 23.017, respectively.Conclusion: Clinical indicators including albumin, globular proteins, chloride, red blood cell count, serum phosphorus, percentage of lymphocyte population, blood urea nitrogen, serum creatinine, platelet distribution width, indirect bilirubin, and serum calcium, as well as socio-demographic factors including the family economy, clinical course, and treatment, may affect coronary heart disease patients’ HRQoL.Keywords: quality of life, coronary heart disease, socio-demographic factors, clinical indicators, scale